Pedagogy of Peace In Practical Theology. Relevance and Opportunities of Religious Educative Processes for an Education and Formation for Peace (Teología, 2016)
This presentation inquires if education for peace is possible, in what way, and which role can the processes of education play in that way. Unlike the 60’s through the 80’s, nowadays education towards peace is not an aim of much importance in German speaking countries. This is surprising considering the present relevance of the subject. After reflecting on the importance and foundations of education towards peace, the author mentions the practical and social skills that are necessary for the establishment and maintenance of peace. These skills can be developed through education, socialization and scholarly training in the primary and secondary process of socialization. The essential aim is the development of a global solidarity which would contribute to mutual binding relationships and mutual recognition among people from different cultures and religions.
Keywords: Peace Pedagogy; Peace Education; Competence; Solidarity; Mutual Recognition